Differentially expressed genes in oesophageal cancer - Wamunyokoli, Fred Alexander Wafula (Division of Medical Biochemistry, 2024)
Oesophageal cancer (OC) is a leading cause of cancer death in the black population in South Africa. The lifetime risk of the disease amongst black males is 1 in 59. High incidence areas are the Transkei, Ciskei and KwaZulu-Natal where it is responsible for over 45 of all malignancies. Cancer develops through a multistep process of genomic instability of clonal evolution. Several oncogenes, tumour suppressor genes and transcription factors have been shown to be altered in oesophageal cancer. Their role however, in the development and/or susceptibility to the development of oesophageal cancer is poorly understood. The aim if this project is to identify candidate genes that are differentially expressed in oesophageal cancer patients with a view to understanding the development of oesophageal cancer. The ultimate objective of the project is to use this data to develop possible biomarkers for the disease.